(Re)constructing state power and livelihoods through the Laos-China railway project - Suhardiman, Diana; DiCarlo, J.; Keovilignavong, Oulavanh; Rigg, J.; Nicol, Alan (Elsevier, 2021)
This paper examines the governance and implementation of land compensation for the Laos-China Railway (LCR). It brings to light the central government’s strategy to use compensation rules and procedures as its means to extend its spatial power across the provinces, districts, and villages that are affected by the railway construction. We examine both the manifestations and effects of state power through the formulation and implementation of land compensation procedures. Taking Naxang village in Chomphet district, Luang Prabang province, in Laos as a case, the paper highlights: 1) how centralized compensation rules and procedures serve as a means for the central government to expand its power; 2) how power relations between central-provincial-district governments (re)shaped the actual project implementation especially pertaining to compensation valuation and payment; and 3) implications for smallholder livelihood options and strategies.